Ti3C2 (at) PDA (at) MMT-Zn composite material and preparation method and composite coating thereof

By using Ti3C2@PDA@MMT-Zn composite material, the synergistic effect of its two-dimensional sheet structure and corrosion inhibitor is used to solve the problem of insufficient anti-corrosion performance of the existing coating, achieving efficient metal anti-corrosion effect and imparting self-repairing performance to the coating.

CN119529580AActive Publication Date: 2025-02-28HEBEI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411861086.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing metal anticorrosion coatings are difficult to meet industrial needs in long-term use, and Ti3C2 has adverse factors such as poor dispersion and easy oxidation in the field of anticorrosion, which limits its further application.

Method used

Ti3C2@PDA@MMT-Zn composite material is used to form a maze effect to extend the diffusion path of corrosive ions through the two-dimensional sheet structure of Ti3C2, and the corrosion inhibition effect of Zn2+ and PDA is used to jointly improve the corrosion resistance of the coating.

Benefits of technology

Effectively improve the physical barrier properties and corrosion resistance of the coating, impart self-repairing performance, good dispersion and compatibility to the coating, and achieve long-term and efficient corrosion inhibition and anti-corrosion effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529580A_ABST
    Figure CN119529580A_ABST
Patent Text Reader

Abstract

The invention provides a Ti3C2 (at) PDA (at) MMT-Zn composite material, a preparation method thereof and a composite coating. The Ti3C2 (at) PDA (at) MMT-Zn composite material is prepared from the following components in parts by mass: 0.2 part of Ti3C2, 0.2 part of MMT, 0.2 part of a zinc nitrate corrosion inhibitor, 0.2 part of dopamine hydrochloride, 0.5 part of a trihydroxymethyl aminomethane Tris buffer solution, 0.1 part of a pH regulator and 120 parts of deionized water. Wherein the Ti3C2 two-dimensional nano material is obtained by taking Ti3AlC2 as a precursor and an HF aqueous solution as an etching system through mixing and stirring. According to the Ti3C2 (at) PDA (at) MMT-Zn composite material disclosed by the invention, not only can the dispersity and compatibility of the composite material in an epoxy coating be ensured, but also the physical shielding effect of a two-dimensional material and the active self-repairing performance of a corrosion inhibitor can be effectively combined to synergistically improve the corrosion resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal protection technology, and in particular to a Ti3C2@PDA@MMT-Zn composite material. The present invention also relates to a preparation method of the Ti3C2@PDA@MMT-Zn composite material. The present invention also relates to a composite coating having the Ti3C2@PDA@MMT-Zn composite material. Background Art

[0002] Metals and their alloy materials are widely used in various industries due to their excellent mechanical properties. However, corrosion is an inevitable problem faced by metal materials during use. The corrosion problem of metals has caused huge waste of resources, economic losses and safety hazards to the country and society, and has always been one of the problems that urgently need to be solved worldwide. In response to the corrosion problem of steel, domestic and foreign scientists have never stopped their research and reported a variety of anti-corrosion methods and technologies: including electrochemical protection, adding corrosion inhibitors, and applying anti-corrosion coatings. Among them, applying an anti-corrosion coating on the metal surface is the simplest and most efficient method for metal corrosion prevention.

[0003] Organic coatings are generally considered to be an insulating layer that protects metals from corrosion by preventing or delaying the penetration of aqueous solutions into the interface between the base metal and the coating. However, aqueous solutions can always penetrate into the coating through the swelling of the coating and the micropores and cracks left on the surface and inside of the coating due to the volatilization of organic solvents, resulting in the long-term protective effect of organic coatings being difficult to meet industrial needs. Therefore, some additives such as nanofillers (SiO2, ZnO, hydrotalcite, montmorillonite (MMT), graphene, etc.) are selected to be added to the coating to improve the physical shielding properties of the organic coating and the protective performance of the coating.

[0004] MMT is a clay composed of nanometer-thick silicate sheets. Its basic structural unit is a 2:1 layered structure consisting of two layers of silicon-oxygen periphery sheets sandwiched between a layer of aluminum-oxygen octahedron sheets. MMT has attracted much attention in the coating field due to its unique layered structure and large specific surface area.

[0005] As a high aspect ratio two-dimensional sheet nanofiller, Ti3C2 can be used to prepare anti-corrosion films with good anti-permeability due to its excellent spatial barrier effect, and can also be added as a filler to organic anti-corrosion coatings to fill the defects produced by the resin during the curing process and significantly extend the service life of the coating. However, at present, the research on Ti3C2 in the field of corrosion protection is still in its early stages, and there are still unfavorable factors such as poor dispersibility and easy oxidation, which limit its further application. Summary of the invention

[0006] In view of this, the present invention aims to propose a Ti3C2@PDA@MMT-Zn composite material.

[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0008] A Ti3C2@PDA@MMT-Zn composite material, comprising the following components by mass fraction: 0.2 parts of Ti3C2, 0.2 parts of MMT, 0.2 parts of zinc nitrate corrosion inhibitor, 0.2 parts of dopamine hydrochloride, 0.5 parts of tris(hydroxymethyl)aminomethane) Tris buffer solution, 0.1 parts of pH regulator, and 120 parts of deionized water;

[0009] Among them, Ti3C2 two-dimensional nanomaterials are obtained by mixing and stirring with Ti3AlC2 as a precursor and HF aqueous solution as an etching system.

[0010] Compared with the prior art, the present invention has the following advantages:

[0011] The Ti3C2@PDA@MMT-Zn composite material described in the present invention uses Ti3C2 as the matrix material. Its small size effect can fill the pores of the coating and increase the density of the coating. The two-dimensional layer structure of Ti3C2 can form a maze effect in the coating to extend the diffusion path of the corrosion-causing ions, thereby effectively improving the physical barrier properties of the coating and improving the passive shielding properties of the coating.

[0012] Moreover, Zn in Ti3C2@PDA@MMT-Zn composites 2+ Both MMT-Zn and PDA have certain corrosion inhibition effects and can synergistically improve the anti-corrosion performance of the coating. When the coating is damaged, MMT-Zn can release Zn through ion exchange. 2+ Corrosion inhibitors slow down metal corrosion, while the functional groups on the surface of PDA can react with Fe 2+ or Fe 3+ The chelate is formed and adsorbed on the damaged part of the coating, and the released Zn 2+ The corrosion inhibitors work synergistically to form a passivation film on the surface of the metal substrate, preventing further corrosion, improving the anti-corrosion performance of the coating, and giving the coating certain self-healing properties.

[0013] At the same time, PDA has strong adhesion. After being adsorbed on the surface of Ti3C2, on the one hand, it improves the antioxidant properties of two-dimensional Ti3C2. On the other hand, due to the presence of amino and hydroxyl groups in the molecule, it also enhances the compatibility and dispersibility of the composite material with epoxy resin, thereby improving the bonding strength between the coating and the substrate.

[0014] In summary, the Ti3C2@PDA@MMT-Zn composite material can not only ensure its dispersibility and compatibility in the epoxy coating, but also effectively combine the physical shielding effect of the two-dimensional material and the active self-healing properties of the corrosion inhibitor to synergistically improve the anti-corrosion performance of the coating.

[0015] Another object of the present invention is to provide a method for preparing a Ti3C2@PDA@MMT-Zn composite material, the preparation method comprising:

[0016] Step A, preparing Ti3C2 two-dimensional nanomaterial powder: slowly adding a certain mass of Ti3AlC2 into a certain mass fraction of HF aqueous solution for etching reaction, washing with deionized water until pH>6, removing the lower layer of precipitate, cooling and drying, and obtaining Ti3C2 two-dimensional nanomaterial powder;

[0017] Step B, preparation of Ti3C2@PDA@MMT-Zn composite material:

[0018] First, the Ti3C2 two-dimensional nanomaterial powder prepared in step A is dispersed in a Tris-HCl buffer solution with a pH of 8.5, dopamine powder is added, and magnetic stirring is performed for a certain period of time to obtain a suspension of the Ti3C2@PDA composite material;

[0019] Next, the obtained suspension of Ti3C2@PDA composite material was centrifuged, the lower precipitate was removed and washed with distilled water, and then redispersed into a suspension containing a certain concentration of MMT and zinc nitrate corrosion inhibitor, and the pH value of the system was adjusted to 3-4, and stirring was continued for a certain period of time, wherein N2 protective gas was introduced during the stirring process;

[0020] Finally, the suspension was centrifuged, the lower precipitate was removed and washed with ethanol and distilled water, and then freeze-dried to obtain the Ti3C2@PDA@MMT-Zn composite material.

[0021] Furthermore, the mass fraction of the HF aqueous solution in step A is 20-50%.

[0022] Furthermore, in step A, the temperature of the etching reaction is between 20-40° C., and the time of the etching reaction is between 12-48 hours.

[0023] Furthermore, in the step B, a certain amount of tris(hydroxymethyl)aminomethane Tris is dispersed in deionized water, a pH adjuster is added to make the pH value of the solution 8.5, and the stirring time is 12-48 hours to obtain a Tris-HCl buffer solution.

[0024] Furthermore, in step B, the molar ratio of Ti3C2 powder to MMT is between 0.5 and 2.0.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] The preparation method of the Ti3C2@PDA@MMT-Zn composite material described in the present invention can ensure the dispersibility and compatibility of the Ti3C2@PDA@MMT-Zn composite material in the epoxy coating, and can effectively combine the physical shielding effect of the two-dimensional material and the active self-repairing performance of the corrosion inhibitor to synergistically improve the corrosion resistance of the coating.

[0027] In addition, another object of the present invention is to provide a composite coating, wherein the composite coating comprises the Ti3C2@PDA@MMT-Zn composite material as described above, and the composite coating is prepared by the following method:

[0028] A Ti3C2@PDA@MMT-Zn composite material with a mass fraction of 0.2-2wt% is added to a waterborne epoxy resin, stirred for 3-5 minutes, and then ultrasonically treated for 5-10 minutes to obtain a composite coating.

[0029] The composite coating of the present invention not only has good dispersibility and compatibility with waterborne epoxy resin by adding Ti3C2@PDA@MMT-Zn composite material, but also can realize Zn 2+ The corrosion inhibitor is stimulated-response released in different environmental systems such as acid, alkali and salt. The water-based epoxy composite coating prepared by using it as a functional anti-corrosion filler can make full use of the physical shielding effect of two-dimensional Ti3C2 materials, the ion exchangeability of montmorillonite, polydopamine and Zn 2+ The corrosion inhibitor effect synergistically improves the anti-corrosion performance of the composite coating, so that the composite coating has both active and passive protection functions and certain self-repairing properties, achieving long-term and efficient anti-corrosion effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0031] Figure 1 The dispersion behaviors of Ti3C2 and Ti3C2@PDA@MMT-Zn composite materials described in the embodiments of the present invention in epoxy resin slurry at different times;

[0032] Figure 2 Zn in the Ti3C2@PDA@MMT-Zn composite material described in the embodiment of the present invention 2+ Release curves in different system environments;

[0033] Figure 3Bode diagrams of the blank epoxy coating according to the embodiment of the present invention immersed in 3.5% NaCl for different time periods;

[0034] Figure 4 Bode diagram of the Ti3C2@PDA@MMT-Zn composite epoxy coating described in the embodiment of the present invention immersed in 3.5% NaCl for different time periods;

[0035] Figure 5 The Bode diagram of the scratched blank epoxy coating according to the embodiment of the present invention immersed in 3.5% NaCl for 72 hours;

[0036] Figure 6 This is the Bode diagram of the scratched Ti3C2@PDA@MMT-Zn composite epoxy coating described in the embodiment of the present invention immersed in 3.5% NaCl for 72 hours;

[0037] Figure 7 Digital photos and SEM photos of the scratched blank epoxy coating and the composite epoxy coating with Ti3C2@PDA@MMT-Zn added described in the embodiments of the present invention immersed in 3.5% NaCl for 72 hours; DETAILED DESCRIPTION

[0038] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0039] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0040] The present embodiment relates to a Ti3C2@PDA@MMT-Zn composite material. In terms of overall design, the Ti3C2@PDA@MMT-Zn composite material includes the following components in mass fractions: Ti3C2: 0.2 parts, MMT: 0.2 parts, zinc nitrate corrosion inhibitor: 0.2 parts, dopamine hydrochloride: 0.2 parts, tris(hydroxymethyl)aminomethane) Tris buffer solution: 0.5 parts, pH regulator: 0.1 parts, and deionized water 120 parts;

[0041] Among them, Ti3C2 two-dimensional nanomaterials are obtained by mixing and stirring with Ti3AlC2 as a precursor and HF aqueous solution as an etching system.

[0042] The Ti3C2@PDA@MMT-Zn composite material of this embodiment uses the two-dimensional material Ti3C2 as the matrix, and its small size effect can be used to fill the pores of the coating to increase the density of the coating. The layered structure of Ti3C2 can form a maze effect in the coating, extending the diffusion path of the corrosion-causing ions, thereby improving the physical shielding performance of the coating, that is, improving the passive shielding performance of the coating.

[0043] Moreover, the MMT-Zn with ion exchange in the Ti3C2@PDA@MMT-Zn composite material can release Zn with corrosion inhibition through ion exchange. 2+ , can give the coating self-healing properties, and the synergistic effect with polydopamine can greatly improve the coating's anti-corrosion performance against metals. At the same time, the introduction of polydopamine in the composite material not only improves the dispersibility of Ti3C2 in epoxy resin, but also improves its antioxidant properties.

[0044] Therefore, the Ti3C2@PDA@MMT-Zn composite material can not only ensure its dispersibility and compatibility in the epoxy coating, but also effectively combine the physical shielding effect of the two-dimensional material and the active self-healing performance of the corrosion inhibitor to synergistically improve the anti-corrosion performance of the coating.

[0045] With respect to the Ti3C2@PDA@MMT-Zn composite material described above in this embodiment, this embodiment also proposes a method for preparing the Ti3C2@PDA@MMT-Zn composite material, and the overall design of the preparation method mainly includes:

[0046] Step A, preparing Ti3C2 two-dimensional nanomaterial powder: slowly adding a certain mass of Ti3AlC2 powder into a certain mass fraction of HF aqueous solution for etching reaction, and washing with deionized water until the pH is greater than 6, removing the lower layer of precipitate and freeze-drying it to obtain Ti3C2 two-dimensional nanomaterial powder.

[0047] Step B, preparation of Ti3C2@PDA@MMT-Zn composite material:

[0048] First, the Ti3C2 two-dimensional nanomaterial powder prepared in step A is dispersed in a Tris-HCl buffer solution with a pH of about 8.5, dopamine powder is added, and magnetic stirring is performed for a certain period of time, for example, 24 hours, to obtain a suspension of the Ti3C2@PDA composite material.

[0049] Next, the obtained suspension of Ti3C2@PDA composite material was centrifuged, the lower precipitate was removed and washed with distilled water, and then redispersed into a suspension containing a certain concentration of MMT and zinc nitrate corrosion inhibitor, and the pH value of the system was adjusted to 3-4, and stirring was continued for a certain period of time, wherein N2 protective gas was introduced during the stirring process.

[0050] Finally, the suspension was centrifuged, the lower precipitate was removed and washed with ethanol and distilled water, and then freeze-dried to obtain the Ti3C2@PDA@MMT-Zn composite material.

[0051] The mass fraction of the HF aqueous solution in step A is 20-50%, and in the specific preparation, the mass fraction of the HF aqueous solution can be 20%, 25%, 30%, 35%, 40%, 45% or 50%.

[0052] In addition, the etching reaction temperature in step A is between 20-40°C, and the etching reaction time is between 12-48h. In specific preparation, the etching reaction temperature can be set to, for example, 20°, 25°, 30°, 35° or 40°, and the etching reaction time can be set to, for example, 12h, 15h, 18h, 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h or 40h.

[0053] In addition, in the above step B, a certain amount of tris (hydroxymethyl)aminomethane (Tris) is dispersed in deionized water, a pH adjuster is added to make the pH value 8.5, and the stirring time is 12-48 hours to obtain a Tris-HCl buffer solution. In addition, the suspension of Ti3C2, MMT and zinc salt is mixed and magnetically stirred for 12-48 hours, and the temperature is controlled between 25-100°C.

[0054] As a preferred embodiment, in the present invention, the molar ratio of Ti3C2 powder to MMT in step B is between 0.5-2.0, and in the specific preparation, the molar ratio of Ti3C2 powder to MMT can be, for example, 0.5, 0.8, 1.0, 1.5 or 2.0.

[0055] Based on the preparation method introduced above, the preparation of the Ti3C2@PDA@MMT-Zn composite material of this embodiment will be specifically described with multiple examples below.

[0056] Example 1

[0057] This embodiment relates to the preparation of Ti3C2@PDA@MMT-Zn composite material, and the specific preparation steps are as follows:

[0058] (1) 1.0 g Ti3AlC2 was slowly added into 30 ml 40% HF at 35°C for 24 h of etching reaction. Then, the mixture was centrifuged and washed several times with deionized water until pH>6. The lower precipitate was removed and freeze-dried to obtain Ti3C2 two-dimensional nanomaterials.

[0059] (2) Weigh 1.0 g of the Ti3C2 powder prepared in the above step and disperse it in 80 ml of deionized water. Add 0.5 g of dopamine hydrochloride and 20 ml of Tris-HCl buffer solution, adjust the pH to 8.5, rotate at 600 rpm, and stir magnetically for 24 h. Centrifuge the mixed solution, wash the lower precipitate with anhydrous ethanol and deionized water until the pH is neutral, and then freeze-dry to obtain a Ti3C2@PDA composite material.

[0060] (3) Weigh 0.5g MMT powder and disperse it in 100ml 1mol / L zinc nitrate solution, adjust the pH value of the system to 3-4, and add 1.0g Ti3C2@PDA powder prepared, the reaction temperature is 30℃, magnetic stirring is carried out for 12h, and N2 protective gas is introduced during the stirring process. Then, the suspension is centrifuged and washed until the pH is neutral, and the precipitate is freeze-dried and ground to obtain Ti3C2@PDA@MMT-Zn composite material.

[0061] The Ti3C2@PDA@MMT-Zn composite material prepared above was added into waterborne epoxy resin with a mass fraction of 0.5wt%, stirred for 3-5min, and then ultrasonicated for 5-10min to obtain a composite coating, which was then coated on a Q235 steel plate.

[0062] Example 2

[0063] (1) 1.0 g Ti3AlC2 was slowly added into 30 ml 50% HF and etched at 25°C for 36 h. The mixture was then centrifuged and washed several times with deionized water until the pH was greater than 6. The lower precipitate was removed and freeze-dried to obtain Ti3C2 two-dimensional nanomaterials.

[0064] (2) Weigh 1.0 g of the Ti3C2 powder prepared in the above step and disperse it in 80 ml of deionized water. Add 0.5 g of dopamine hydrochloride and 20 ml of Tris-HCl buffer solution, adjust the pH to 8.1, rotate at 600 rpm, and stir magnetically for 12 h. Centrifuge the mixed solution, wash the lower precipitate with anhydrous ethanol and deionized water until the pH is neutral, and then freeze-dry to obtain a Ti3C2@PDA composite material.

[0065] (3) Weigh 1.0g MMT powder and disperse it in 100ml 1mol / L zinc nitrate solution, adjust the pH value of the system to 3-4, and add 1.0g Ti3C2@PDA powder prepared, the reaction temperature is 50℃, magnetic stirring is carried out for 24h, and N2 protective gas is introduced during the stirring process. Then, the suspension is centrifuged and washed until the pH is neutral, and the precipitate is freeze-dried and ground to obtain Ti3C2@PDA@MMT-Zn composite material.

[0066] The Ti3C2@PDA@MMT-Zn composite material prepared above was added to the waterborne epoxy resin with a mass fraction of 1.5wt%, stirred for 3-5min, and then ultrasonicated for 5-10min to obtain a composite coating. The composite coating was then applied to a Q235 steel plate.

[0067] Example 3

[0068] (1) 1.0 g Ti3AlC2 was slowly added into 20 ml 50% HF and etched at 30°C for 24 h. The mixture was then centrifuged and washed several times with deionized water until the pH was greater than 6. The lower precipitate was removed and freeze-dried to obtain Ti3C2 two-dimensional nanomaterials.

[0069] (2) Weigh 1.0 g of the Ti3C2 powder prepared in the above step and disperse it in 80 ml of deionized water. Add 0.5 g of dopamine hydrochloride and 20 ml of Tris-HCl buffer solution, adjust the pH to 8.2, rotate at 600 rpm, and stir magnetically for 36 h. Centrifuge the mixed solution, wash the lower precipitate with anhydrous ethanol and deionized water until the pH is neutral, and then freeze-dry to obtain a Ti3C2@PDA composite material.

[0070] (3) Weigh 1.5g MMT powder and disperse it in 100ml 1mol / L zinc nitrate solution, adjust the pH value of the system to 3-4, and add 1.0g Ti3C2@PDA powder prepared therein, the reaction temperature is 75℃, magnetic stirring is carried out for 48h, and N2 protective gas is introduced during the stirring process. Then, the suspension is centrifuged and washed until the pH is neutral, and the precipitate is freeze-dried and ground to obtain Ti3C2@PDA@MMT-Zn composite material.

[0071] The Ti3C2@PDA@MMT-Zn composite material prepared above was added to the waterborne epoxy resin with a mass fraction of 1.0wt%, stirred for 3-5min, and then ultrasonicated for 5-10min to obtain a composite coating, and then the composite coating was coated on a Q235 steel plate.

[0072] Example 4

[0073] (1) 1.0 g of Ti3AlC2 was slowly added into 10 ml of 30% HF and etched at 40°C for 48 h. The mixture was then centrifuged and washed several times with deionized water until the pH was greater than 6. The lower precipitate was removed and freeze-dried to obtain Ti3C2 two-dimensional nanomaterials.

[0074] (2) Weigh 1.0 g of the Ti3C2 powder prepared in the above step and disperse it in 80 ml of deionized water. Add 0.5 g of dopamine hydrochloride and 20 ml of Tris-HCl buffer solution, adjust the pH to 8.3, rotate at 600 rpm, and stir magnetically for 48 h. Centrifuge the mixed solution, wash the lower precipitate with anhydrous ethanol and deionized water until the pH is neutral, and then freeze-dry to obtain a Ti3C2@PDA composite material.

[0075] (3) Weigh 2.0g MMT powder and disperse it in 100ml 1mol / L zinc nitrate solution, adjust the pH value of the system to 3-4, and add 1.0g Ti3C2@PDA powder prepared, the reaction temperature is 50℃, magnetic stirring is carried out for 24h, and N2 protective gas is introduced during the stirring process. Then, the suspension is centrifuged and washed until the pH is neutral, and the precipitate is freeze-dried and ground to obtain Ti3C2@PDA@MMT-Zn composite material.

[0076] The Ti3C2@PDA@MMT-Zn composite material prepared above was added to the epoxy resin with a mass fraction of 0.5wt%, stirred for 3-5min, and then ultrasonicated for 5-10min to obtain a composite coating, and then the composite coating was coated on a Q235 steel plate.

[0077] Example 5

[0078] (1) 1.0 g of Ti3AlC2 was slowly added into 25 ml of 40% HF and etched at 20°C for 20 h. The mixture was then centrifuged and washed several times with deionized water until the pH was greater than 6. The lower precipitate was removed and freeze-dried to obtain Ti3C2 two-dimensional nanomaterials.

[0079] (2) Weigh 1.0 g of the Ti3C2 powder prepared in the above step and disperse it in 80 ml of deionized water. Add 0.5 g of dopamine hydrochloride and 20 ml of Tris-HCl buffer solution, adjust the pH to 8.4, rotate at 600 rpm, and stir magnetically for 24 h. Centrifuge the mixed solution, wash the lower precipitate with anhydrous ethanol and deionized water until the pH is neutral, and then freeze-dry to obtain a Ti3C2@PDA composite material.

[0080] (3) Weigh 1.0g MMT powder and disperse it in 100ml 1mol / L zinc nitrate solution, adjust the pH value of the system to 3-4, and add 1.0g Ti3C2@PDA powder prepared therein, the reaction temperature is 50℃, magnetic stirring is carried out for 48h, and N2 protective gas is introduced during the stirring process. Then, the suspension is centrifuged and washed until the pH is neutral, and the precipitate is freeze-dried and ground to obtain Ti3C2@PDA@MMT-Zn composite material.

[0081] The Ti3C2@PDA@MMT-Zn composite material prepared above was added into waterborne epoxy resin with a mass fraction of 1.5wt%, stirred for 3-5min, and then ultrasonicated for 5-10min to obtain a composite coating, which was then coated on a Q235 steel plate.

[0082] In the present invention, the Ti3C2@PDA@MMT-Zn composite material prepared by the above-mentioned preparation example is etched by HF to obtain a Ti3C2 two-dimensional layered material, and the Ti3C2 two-dimensional layered material is modified by polydopamine to improve its corrosion resistance, oxidation resistance, and its dispersibility and compatibility in epoxy matrix. Then, an ion exchange type MMT-Zn functional corrosion inhibitor is adsorbed on its surface by electrostatic interaction to obtain a Ti3C2@PDA@MMT-Zn composite material.

[0083] Then, the Ti3C2@PDA@MMT-Zn composite material was added into waterborne epoxy resin as a functional filler to obtain a composite coating with Ti3C2@PDA@MMT-Zn.

[0084] The preparation method of the Ti3C2@PDA@MMT-Zn composite material of the present invention can ensure the dispersibility and compatibility of the Ti3C2@PDA@MMT-Zn composite material in the epoxy coating, and can effectively combine the physical shielding effect of the two-dimensional material and the active self-repairing performance of the corrosion inhibitor to synergistically improve the anti-corrosion performance of the coating. It also has good slow-controlled release characteristics and multiple response performances in different system environments (acid, alkali, salt). At the same time, the water-based epoxy composite coating prepared by using it as a filler has excellent anti-corrosion performance and certain self-repairing performance.

[0085] In order to better illustrate that the Ti3C2@PDA@MMT-Zn composite material of the present invention has good sustained-release characteristics and multiple response performances in different system environments (acid, alkali, salt), the following experiments and experimental results are used to explain it in detail.

[0086] (1) Dispersion performance

[0087] A certain amount of Ti3C2 and Ti3C2@PDA@MMT-Zn samples were weighed and added to epoxy resin, where the amount of each sample added was 0.5wt% of the epoxy resin. The two samples were dispersed in the epoxy resin by ultrasonic treatment, and their dispersibility in the epoxy resin slurry was investigated. The results are shown in Figure 1 shown.

[0088] from Figure 1It can be seen that ultrasonic treatment can make both samples dispersed evenly in epoxy resin slurry in a short time (1h). However, when the standing time reaches 360h, precipitation can be clearly observed at the bottom of the epoxy slurry with Ti3C2 added, while no obvious precipitation was observed in the epoxy slurry with Ti3C2@PDA@MMT-Zn added, which shows that Ti3C2@PDA@MMT-Zn composite material has better dispersibility than Ti3C2 material. This is because polydopamine contains a large number of hydrophilic catechol groups and amino groups, which improves the dispersibility of the material in epoxy resin slurry.

[0089] (2) Release performance

[0090] First, weigh 0.1g Ti3C2@PDA@MMT-Zn material and add it to 100ml solution of different environmental systems (acid, alkali, salt). Take out 5ml release medium at appropriate time and add equal amount of deionized water of different pH to it. Then, use UV-visible spectrophotometer to measure zinc ion concentration of release medium at different time, and sort out the data to get zinc ion release curve. The result is as follows: Figure 2 shown.

[0091] like Figure 2 As shown in (a), in a neutral solution, Zn in Ti3C2@PDA@MMT-Zn 2+ The release rate is very slow, and the release amount is only about 3%. This may be due to the positively charged Zn 2+ There is an electrostatic force between the negatively charged MMT layer; in acidic solution, its release rate increases significantly and gradually increases with the decrease of pH value.

[0092] from Figure 2 It can be observed in (b) that alkali can also accelerate the Zn in Ti3C2@PDA@MMT-Zn 2+ The release rate increases with the increase of OH- concentration in the solution. Figure 2 (c) Zn in Ti3C2@PDA@MMT-Zn 2+ The release rate in NaCl solution is significantly higher than that in distilled water, and it gradually increases with the increase of NaCl concentration. This phenomenon is due to the strong ion exchangeability of MMT. 2+ It can exchange ions with Na+ in the solution and transfer a large amount of Zn 2+ Released into solution.

[0093] In addition, in order to better illustrate the anti-corrosion performance and sustained-release performance of the Ti3C2@PDA@MMT-Zn composite material, in the present invention, the Ti3C2@PDA@MMT-Zn composite material is added to the epoxy resin, and then the classic three-electrode system (Q235 steel plate coated with epoxy resin is the working electrode, the saturated calomel electrode is the reference electrode, and the platinum sheet electrode is the counter electrode) is used. The electrochemical impedance test is performed on the coated steel plate by immersing it in a 3.5% NaCl solution for different time periods using an electrochemical workstation. The results are shown in FIG. Figures 3 to 7 shown.

[0094] from Figure 3 It can be seen that the impedance value of the blank epoxy coating at the initial immersion stage is 10 7 Ω·cm 2 As the soaking time increases, the impedance value decreases continuously. When the soaking time reaches 110 days, the impedance value drops to 10 6 Ω·cm 2 , indicating that the corrosive medium has penetrated into the coating / metal substrate interface and corrosion has occurred. For the composite coating with Ti3C2@PDA@MMT-Zn composite material ( Figure 4 ), the impedance value is 10 at the initial immersion stage 10 Ω·cm 2 , which is 3 orders of magnitude higher than that of the blank coating, indicating that the introduction of the Ti3C2@PDA@MMT-Zn composite material in the coating improves the anti-corrosion performance of the coating. At the same time, during the immersion process, its impedance value has been maintained at a high level (10 10 Ω·cm 2 ), which are higher than the impedance value of the blank coating, indicating that the composite coating with the addition of Ti3C2@PDA@MMT-Zn composite material has good anti-corrosion performance.

[0095] In addition, the present invention also carried out scratch tests on the composite coating with Ti3C2@PDA@MMT-Zn and the blank coating, and the corresponding impedance test was as follows: Figure 5 and Figure 6 As shown in the figure, the scratched blank epoxy coating and the scratched Ti3C2@PDA@MMT-Zn composite coating were immersed in 3.5% NaCl for 72h. Figure 7 shown.

[0096] Depend on Figure 5 It can be seen that during the entire immersion period, the impedance value of the scratch blank coating in the low-frequency region was about 4.3 on the first day of immersion, but after immersion for 72 hours, the value of the scratch blank coating dropped to about 3.5. Figure 6), the impedance value in the low frequency region on the first day of immersion is about 4.5, and as the immersion time increases, the impedance value in the low frequency region decreases less, and when the immersion time is 72h, the impedance value in the low frequency region is about 4.2. It can be seen that the composite coating with the addition of Ti3C2@PDA@MMT-Zn composite material exhibits good self-healing and anti-corrosion properties.

[0097] And, through the photos of scratches soaked in time such as Figure 7 As shown, it can be seen that there are no obvious corrosion products on the metal matrix at the scratch of the composite coating, indicating that the zinc ions and dopamine released from the Ti3C2@PDA@MMT-Zn composite material form a protective film on the metal surface to prevent further corrosion. That is, the Ti3C2@PDA@MMT-Zn composite material can release corrosion inhibitors in the coating and improve the anti-corrosion performance of the coating.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A Ti3C2@PDA@MMT-Zn composite material, characterized in that :: The Ti3C2@PDA@MMT-Zn composite material includes the following components by mass fraction: Ti3C2: 0.2 parts, MMT: 0.2 parts, zinc nitrate corrosion inhibitor: 0.2 parts, dopamine hydrochloride: 0.2 parts, tris (hydroxymethyl)aminomethane Tris buffer solution: 0.5 parts, pH regulator: 0.1 parts, and deionized water 120 parts; Among them, Ti3C2 two-dimensional nanomaterials are obtained by mixing and stirring with Ti3AlC2 as a precursor and HF aqueous solution as an etching system.

2. A method for preparing a Ti3C2@PDA@MMT-Zn composite material, characterized in that: The preparation method comprises: Step A, preparing Ti3C2 two-dimensional nanomaterial powder: slowly adding a certain mass of Ti3AlC2 into a certain mass fraction of HF aqueous solution for etching reaction, washing with deionized water until pH>6, removing the lower layer of precipitate, cooling and drying, and obtaining Ti3C2 two-dimensional nanomaterial powder; Step B, preparation of Ti3C2@PDA@MMT-Zn composite material: First, the Ti3C2 two-dimensional nanomaterial powder prepared in step A is dispersed in a Tris-HCl buffer solution with a pH of 8.5, dopamine powder is added, and magnetic stirring is performed for a certain period of time to obtain a suspension of the Ti3C2@PDA composite material; Next, the obtained suspension of Ti3C2@PDA composite material was centrifuged, the lower precipitate was removed and washed with distilled water, and then redispersed into a suspension containing a certain concentration of MMT and zinc nitrate corrosion inhibitor, and the pH value of the system was adjusted to 3-4, and stirring was continued for a certain period of time, wherein N2 protective gas was introduced during the stirring process; Finally, the suspension was centrifuged, the lower precipitate was removed and washed with ethanol and distilled water, and then freeze-dried to obtain the Ti3C2@PDA@MMT-Zn composite material.

3. The method for preparing the Ti3C2@PDA@MMT-Zn composite material according to claim 2, characterized in that: The mass fraction of the HF aqueous solution in step A is 20-50%.

4. The method for preparing the Ti3C2@PDA@MMT-Zn composite material according to claim 2, characterized in that: The temperature of the etching reaction in step A is between 20-40° C., and the time of the etching reaction is between 12-48 hours.

5. The method for preparing the Ti3C2@PDA@MMT-Zn composite material according to claim 2, characterized in that: In the step B, a certain amount of tris (hydroxymethyl)aminomethane (Tris) is dispersed in deionized water, a pH adjuster is added to adjust the pH value of the solution to 8.5, and the stirring time is 12-48 hours to obtain a Tris-HCl buffer solution.

6. The method for preparing the Ti3C2@PDA@MMT-Zn composite material according to claim 2, characterized in that: In the step B, the molar ratio of Ti3C2 powder to MMT is between 0.5 and 2.

0.

7. A composite coating, characterized in that: The composite coating comprises the Ti3C2@PDA@MMT-Zn composite material of claim 1, and the composite coating is prepared by the following method: A Ti3C2@PDA@MMT-Zn composite material with a mass fraction of 0.2-2wt% is added to a waterborne epoxy resin, stirred for 3-5 minutes, and then ultrasonically treated for 5-10 minutes to obtain a composite coating.

Citation Information

Patent Citations

  • Dopamine surface modified two-dimensional nano material and preparation method thereof

    CN107216689A

  • Two-dimensional composite material modified waterborne epoxy zinc-rich composite coating and preparation method and application thereof

    CN111978822A

  • ZIF-8 / MXene PDA composite lubricating material and preparation method thereof

    CN116804159A

  • Alkalified titanium carbide-based composite corrosion inhibitor as well as preparation method and application thereof

    CN117683385A

  • KR20210103216A

Cited By

  • Ti3C2Tx-coated SiO2-BTA-coated ZIF composite material, preparation method, composite coating and application

    CN122188438A